2019
DOI: 10.1177/1756284818822566
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal vitamin D receptor in inflammatory bowel disease: inverse correlation with inflammation but no relationship with circulating vitamin D status

Abstract: Background:The intestinal vitamin D receptor (VDR) remains poorly characterized in patients with inflammatory bowel disease (IBD).Methods:Colonoscopic biopsies and intestinal resection specimens from the terminal ileum, ascending and sigmoid colon, from patients with and without IBD, were analyzed for VDR mRNA quantification by polymerase chain reaction, and protein localization and semi-quantification by immunohistochemistry. The relationship between VDR and intestinal inflammation, serum 25(OH)D and oral vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
1
27
0
2
Order By: Relevance
“…After removing 298 duplicates, 1087 potentially relevant studies were selected on the basis of the abstract, and of these, 119 full texts were assessed for eligibility. In total, 55 publications [16, 18, 2577] were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing 298 duplicates, 1087 potentially relevant studies were selected on the basis of the abstract, and of these, 119 full texts were assessed for eligibility. In total, 55 publications [16, 18, 2577] were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 cohort studies [18, 34, 38, 41, 50–56, 64, 67, 68, 71, 73, 74, 76, 77], 22 case–control studies [16, 2529, 3133, 35, 42, 43, 46, 49, 5963, 66, 69, 70] and 14 cross-sectional studies [30, 36, 37, 39, 40, 44, 45, 47, 48, 57, 58, 65, 72, 75] were included in the analysis. The total number of participants was 5123 patients and 3033 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…As the downstream signaling with expression of cathelicidin, was not reduced in COPD lung tissue, it indicates that VDR functioning was relatively well preserved, even in COPD lungs. As VDR expression is not only affected by inflammatory signals, including cigarette smoking, but also by vitamin serum levels, additional studies are needed to explore VDR expression in the context of COPD [27][28][29]. These studies should also focus on nuclear versus cytoplasmatic localization of VDR as Uh et al reported that cigarette smoke inhibits VDR translocation in alveolar cell line [30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, reduced Ca intake has been associated with diminished VDR mRNA in avians parathyroid gland ( Russell et al., 1993 ). A lower expression of VDR is also reported in many gut-related diseases in chickens and in other species ( Wu et al., 2015 ; Garg et al., 2019 ).…”
Section: Discussionmentioning
confidence: 78%